Causes Of Neonatal Mortality: A Community Based Study Using Verbal Autopsy Tool - Jain, Yashpal; Bansal, Madhav; Tiwari, Rajesh; Kasar, Pradeep Kumar (National Journal of Community Medicine, 2013)
Introduction: Neonatal mortality is increasingly important because the proportion of under-five deaths that occur during the neonatal period is increasing as under-five mortality declines. Because declines in the neonatal mortality rate are slower the share of neonatal deaths among under-five deaths increased from about 36 percent in 1990 to about 43 percent in 2011. There is a need to identify and address the causes of neonatal mortality to achieve the MDG of 31 under five deaths per 1000 live births per year. Objective: To ascertain the causes of neonatal mortality in the area covered by CHC Natwara (Shahpura Block) of Jabalpur district using verbal autopsy method. Materials and Methods: Neonatal deaths registered during the period of 1st April 2005 to 31st March 2006 at CHC Natwara of District Jabalpur of MP were studied. Total 69 neonatal deaths were studied using standard verbal autopsy questionnaire. Causes of deaths were ascertained from the filled in VA questionnaire taking the help of a pediatrician. Results: Mother was main respondent in 50.72% cases followed by father (23.1%). Sepsis was the most important cause of death particularly in the late neonatal period. Birth asphyxia, pneumonia and RDS were the other important causes of death contributing predominantly to the early neonatal deaths. The most important predisposing cause of death was LBW/prematurity. Conclusion: Most of the deaths are directly or indirectly related to infection and nutrition and are therefore amenable to prevention.